The effect of country risk on the return and risk of the optimal investment portfolio - an applied study in the Iraqi stock market for the period (2005-2015) - Hakim Muhsin Al-Rbyey; Meethaq hatef Abid Al-Sada; Noor Sabah Hamid (Iraqi Journal for Administrative Sciences, 2024)
The world has witnessed major changes in the past few decades at all levels, which have presented major challenges faced by business organizations with their various economic activities. Among the most important of these changes and transformations is globalization in all its forms and types, and most economic sectors have become intertwined and linked to each other through blocs and mergers to form giant entities among themselves. In light of such changes, risk was the inherent element of all investments and the movement of money, goods, and services, and therefore the issue of risk specific to each country became a basic basis in determining the destination of local and foreign investors, and risk, along with return, is considered a reference basis in building investment portfolios. The process of building the investment portfolio and the multiple methods on which the construction process is based are of great importance in the financial field and reflect the steps that must be followed to make rational decisions in creating an investment portfolio that balances return and risk for a wide range of financial assets in the financial market. Therefore, this study aimed to build an optimal investment portfolio in the Iraqi Stock Exchange for each year of the specified study years from 2005 until 2015 and to analyze the data of each portfolio separately and the stocks involved in building the optimal portfolio in a simple ranking method. Then, the impact of country risk based on the International Guide to Country Risk (ICGR) on the optimal investment portfolio is measured, expressed as the return and risk of the investment portfolio on an annual basis.